(untitled) (Research, Society and Development, 2025)
Student assistants are professionals assigned to educational institutions who support the daily academic routine of students. Although their duties are exclusively related to the educational field, it is common for students not to recognize these professionals, and, in some cases, student assistants are assigned to other sectors of the institution. This research evaluated the role of the student assistant at the Federal Institute of Ceará (IFCE) and how their duties are understood by students in integrated technical education. This work was classified as a qualitative field research. The research locus comprised the IFCE campuses of Caucaia, Fortaleza, Maracanaú, and Maranguape. A total of 227 students and 25 student assistants were interviewed. The results were obtained through two electronic questionnaires. The analysis of the responses showed that 70.9% of the students claimed to know the position of student assistant, with 44.5% agreeing on the importance of these professionals in the daily operation of the institution. Among the interviewed student assistants, it was observed that 76% are aware of their duties, but, in their perception, the absence of a student assistant on campus compromises the proper functioning of the unit, further highlighting that about 76% of other institutional professionals are unaware of the role of the student assistant. The data demonstrate the need for public policies that expand the presence of these professionals in federal educational institutions and for greater institutional engagement in promoting and recognizing the role of the student assistant as a factor in student retention and success.